MANAJEMEN RANTAI PASOK DAGING AYAM - Septian Adi Dwicahya; Banun Diyah Probowati (Agroindustrial Technology, University of Trunojoyo Madura, 2014)
One very popular analytical framework used lately in increasing the added value and competitiveness of the poultry industry is supply chain management. This study aims to determine how the upstream supply chain, internal supply chain and agro-industry supply chain downstream of chicken meat. The experiment was conducted in the agro-industry in Pasuruan with interviews and observations. Data analysis was performed by descriptive and qualitative nature. The results of this study are in the upstream supply chain system consists of a chicken slaughterhouse unit as the main raw material suppliers of chicken meat that interact directly with chicken meat processing unit in the form of sausage. Internal supply chain in this system is played entirely by agroindustrial processing of chicken meat which acts as processing unit and offender management handling, testing, processing, and storage, which then sends the finished product to the marketing and logistics headquarters. Downstream supply chain includes the supply of finished products such as sausages and nuggets of marketing headquarters to consumers include shops, hypermart, mini markets, supermarkets and franchise fried chicken. The main focus of the downstream supply chain is distributing products according to the needs of each element (companies and consumers).